Safety, effectiveness, and cost of long-acting versus intermediate-acting insulin for type 1 diabetes: Protocol for a systematic review and network meta-analysis - Tricco, Andrea C; Ashoor, Huda M; Soobiah, Charlene; Hemmelgarn, Brenda; Moher, David; Hutton, Brian; Yu, Catherine H; Majumdar, Sumit R; Straus, Sharon E (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Type 1 diabetes mellitus (T1DM) causes progressive destruction of pancreatic beta cells leading to absolute insulin deficiency. Treatment of T1DM requires insulin, and some evidence suggests that longer acting insulin analogues might have a higher effectiveness and greater safety profile compared to intermediate-acting insulin. Our objective is to evaluate the comparative effectiveness, safety, and cost of long-acting insulin versus intermediate-acting insulin through a systematic review and network meta-analysis. Design/methods Studies examining long-acting versus intermediate-acting insulin or placebo preparations for adult T1DM patients will be included. The primary outcome is glycosylated hemoglobin (A1C), and secondary outcomes include emergency department and physician visits, hospital admissions, weight gain, quality of life, microvascular complications (e.g., retinopathy), macrovascular complications (e.g., cardiovascular disease), all-cause mortality, incident cancers, and cost. We will include experimental [randomized clinical trials (RCTs), quasi-RCTs, non-RCTs], quasi-experimental (controlled before-after, interrupted time series), observational (cohort), and cost studies, of any duration of follow-up, conducted during all time periods, and disseminated in any language. We will conduct comprehensive searches of electronic databases from inception onwards, including MEDLINE, Cochrane Central Register of Controlled Trials, and EMBASE. We will also search for difficult to locate and unpublished literature by searching dissertation databases, public health organization websites, and trial registries. After a calibration exercise using our eligibility criteria and data abstraction forms, two reviewers will screen all citations, full-text articles, and abstract data in duplicate. Conflicts will be resolved by team discussion. Using a similar process, the Cochrane Effective Practice and Organization of Care Risk of Bias tool will be used to appraise the risk of bias of experimental and quasi-experimental studies, while the Newcastle Ottawa Scale will be used to assess the methodological quality of cohort studies. If feasible and appropriate, we will conduct a random effects meta-analysis, as well as a network meta-analysis. Discussion Our systematic review will be of utility to healthcare providers, policy-makers, T1DM patients and family members regarding treatment options of long-acting versus intermediate-acting insulin preparations. Trial registration PROSPERO registry number: CRD42013003610